Comparative study of the effect on the neuroendocrine-immune complex and metabolism of drinking monotherapy with Naftussya water and therapy supplemented with "Myroslava" and "Khrystyna" mineral waters - Myroslava Hrytsak; Dariya Popovych; Nataliya Badiuk; Ivanna Hrytsan; Xawery Żukow (Kazimierz Wielki University, 2022)
Background. Earlier in an experiment on rats, we showed that the newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets' spa have neuroendocrine and metabolic effects significantly different from daily water. Adhering to the principle "From experiment to clinic", we continued research in this direction with the participation of patients of the resort. Materials and Methods. The object of clinical-physiological observation were 34 men aged 23-70 years, who underwent rehabilitation treatment of chronic cholecystitis and pyelonephritis in remission in the Truskavets resort. The examination was performed twice, before and after a 7-10-day course of balneotherapy. All patients received bioactive water Naftussya, however, 11 men additionally drank water "Khrystyna", and the other 11 men - water "Myroslava". The subject of the study were the parameters of the neuroendocrine-immune complex and metabolism. Results. The complex balneotherapy by interval use of sulfate-chloride sodium-magnesium mineral waters with Naftusya water causes significant changes in the constellation of neuroendocrine, metabolic and immune parameters, which are different from the effects of Naftusya water monotherapy. Own effects of mineral waters are estimated by modeling. In general, the effects are physiologically favorable and have a normalizing nature. Conclusion. The newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets resort have favorable neuroendocrine, metabolic and immune effects on patients with chronic cholecystitis and pyelonephritis.